2008
DOI: 10.1080/00365540701747119
|View full text |Cite
|
Sign up to set email alerts
|

IgM and avidity of IgG antibodies in primary HHV-6 infections

Abstract: Primary HHV-6 infection could be diagnosed by enzyme immunoassay from a single serum using IgG avidity test based on results obtained from 43 patients, 26 with seroconversion and 17 with variable antibody levels. The avidity was less than 30% in all patients with seroconversion. HHV-6 IgM appeared non-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Second, although the specificity of ELISA IgG determination is 98.8% and its sensitivity is 99.8% (28), data on the specificity and sensitivity of tests for the HHV-6 IgM antibody are contradictory. Parker and Weber (29) reported 98% IgM specificity, but Salonen et al (30) reported 77% sensitivity and 41% specificity. The manufacturer (Panbio) indicates that the kit used in the present study has a 52.5% serological sensitivity and a 87.8% clinical specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although the specificity of ELISA IgG determination is 98.8% and its sensitivity is 99.8% (28), data on the specificity and sensitivity of tests for the HHV-6 IgM antibody are contradictory. Parker and Weber (29) reported 98% IgM specificity, but Salonen et al (30) reported 77% sensitivity and 41% specificity. The manufacturer (Panbio) indicates that the kit used in the present study has a 52.5% serological sensitivity and a 87.8% clinical specificity.…”
Section: Discussionmentioning
confidence: 99%
“…IgG is identified as being of low avidity if there is a reduction in the titre in the specimen analyzed in the assay carried out in denaturing conditions compared with the normal procedure, which indicating primary infection. Methods have been developed to characterize the avidity of IgG against measles [27], rubella [28,29], PVHB19 [30], HHV-6 [31]; EBV [32]; CMV [33], Dengue virus [34,35] and VZV and HSV [29].…”
Section: Indirect Diagnosis: Serologymentioning
confidence: 99%
“…IgG avidity assays are applicable to the diagnosis of primary infection, and permit differentiation between primary and secondary infection in herpes infections, especially those produced by CMV and VZV infections [29], since both diseases may produce specific IgM. In addition, they permit the confirmation of EBV infection [32] by detection of IgM anti-CMV, and are also useful to confirm or exclude primary rubella virus infection in pregnancy by detection of specific IgM [28,36].…”
Section: Indirect Diagnosis: Serologymentioning
confidence: 99%